A systematic review of teacher self-monitoring on implementation of behavioral practices. (April 2017) - Rispoli, Mandy; Zaini, Samar; Mason, Rose; Brodhead, Matthew; Burke, Mack D.; Gregori, Emily
Abstract: Behavioral intervention success relies in part on the accuracy with which interventions are implemented. Self-monitoring may be effective for improving teacher implementation fidelity of behavioral interventions. The purpose of this systematic review was to summarize the research on teacher self-monitoring of behavioral interventions and to summarize the quality of the research according to the Council for Exceptional Children quality indicators. A total of 17 studies were reviewed. Of these, seven met all research quality indicators. Studies are summarized according to: (a) teacher participants, (b) self-monitoring training, (c) self-monitoring practices, and (d) effects of teacher self-monitoring on teacher and student outcomes. Highlights: We conducted a systematic review of teacher self-monitoring on fidelity of behavior practices in the classroom. Current evidence suggest teacher self-monitoring may be a potentially effective means of improving teacher and student outcomes. Seven of 17 studies met all quality indicators, highlighting the need for continued rigorous research in this area.